Takotsubo syndrome triggered by a pleasant emotional event: a case report - Amaro-Palomo, Eder Jonathan (2025)
Takotsubo Syndrome (TTS) is characterized by transient left ventricular dysfunction, often triggered by emotional or physical stress. While negative emotional events are common triggers, positive emotional events can also induce a rare variant known as Happy Heart Syndrome (HHS). This case report describes a 53-year-old male who presented with acute chest pain following a positive emotional stimulus: a birthday call offering him an opportunity to play with his favorite music group. Initial workup suggested an acute myocardial infarction, but coronary angiography revealed no obstruction. Left ventriculography showed the classic apical ballooning pattern of TTS. The patient was diagnosed with HHS. This case underscores the importance of considering positive emotional triggers in the diagnosis of TTS and highlights the need for further research into its diverse presentations and management strategies.